Analisis praktik jaminan fidusia dan permasalahannya: Studi kasus di Kantor PPAT Kota Malang - Tustasari, Rensa Dwi (Maliki Interdisciplinary Journal, 2024)
In the Indonesian legal context, the practice of fiduciary guarantees has become an important part of financial transactions that can provide multiple benefits. Despite being regulated by Law No. 42/1999, the implementation of fiduciary guarantees often faces challenges, one of which is related to the issue of fiduciary guarantee execution. The focus of the author’s study is limited to one of the offices of PPAT Enny Rahaju Widjajanti S.Pd, S.H, M.Kn in Malang city by highlighting the implementation and problems faced regarding fiduciary guarantees, therefore the author is interested in conducting research with the title Analysis of fiduciary guarantee practices and problems: a case study at the Malang city PPAT office. The research method used is empirical juridical research with a qualitative approach. The results show that in practice there are weaknesses in the execution carried out by creditors through debt collector services which sometimes cause new problems between creditors and debtors such as intimidation and violence. Therefore, the notary as a party who understands the law regarding the execution of fiduciary guarantees plays an important role in providing direction in the form of education or socialisation to business actors and related parties regarding Law Number 42 of 1999 concerning Fiduciary and the application of the execution of fiduciary security objects.